“Transcranial direct current stimulation for chronic foot pain: A comprehensive review” - Roberto Tedeschi (eNeurologicalSci)
Background: Chronic foot pain, including conditions such as plantar fasciitis, presents a significant challenge to patients and healthcare providers. Traditional treatments often offer limited relief, prompting exploration of alternative therapies. Transcranial direct current stimulation (tDCS) has emerged as a noninvasive brain stimulation technique with potential for alleviating chronic pain syndromes. Methods: A review was conducted following the JBI methodology and adhering to PRISMA guidelines. Searches were performed in databases including MEDLINE, Cochrane Central, Scopus, and PEDro, supplemented by grey literature sources and expert consultations. Studies were included if they investigated tDCS as an intervention for chronic foot pain, assessed its efficacy, safety, or mechanisms of action, and were published in English. Results: A total of three papers were included in the review. The findings indicate that tDCS holds promise for managing chronic foot pain, including plantar fasciitis. Main results suggest significant reductions in pain intensity and improvements in related outcomes following tDCS treatment. Conclusions: This review underscores the potential of tDCS as an alternative therapy for severe lower-extremity pain, highlighting the need for further research to optimize its parameters and long-term effects. tDCS emerges as a promising neuromodulation approach for chronic foot pain management, offering insights for enhancing patient outcomes and quality of life.